Meningkatkan Produktivitas Menulis Karya Tuliah Ilmiah bagi Mahasiswa di Era Digital - Mega Kusuma Listyotami; Nur Shabrina Reznani (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
The purpose of this devotional activity is 1) to provide participants with knowledge in writing scientific papers, 2) to improve students ability in writing scientific papers, 3) to improve and encourage students in writing scientific papers. The Method used in community service are: by method precentation, question and answer, discussion, and practice of composing scientific paper proposal after participating in this training. The participants have understood the types of scientific papers, the tecnique in writing scientific papers, topic determination and preparation of scientific papers. The results in community service are: 1) provide knowledge to the students of University of Selamat Sri, 2) Student who studied this activity are mostly the final study students, so this material helps students in facing process of completing study, 3) Students to preparing and making scientific papers.